Banjir DKI Jakarta dan Pencalonan Jokowi Menjadi Presiden Ke-7 (Studi Perbandingan Analisis Framing Surat Kabar Harian Suara Merdeka dan Jawa Pos Dalam Memberitakan Dampak Banjir DKI Jakarta Terhadap Pencalonan Jokowi Menjadi Presiden Ke-7 Periode Tanggal 1 hingga 31 Januari 2014) - Rowi, Asep Abdullah; , Budi Santoso, M.Si (2015)
This research is conducted to find out the impact of reporting DKI Jakarta flooded towards Jokowi nominee being the seventh president. Jokowi as a 'media darling' is interested to analyze by Suara Merdeka dan Jawa Pos's news. The aim of this research is finding out the frame used by both newspapers. The data of Suara Merdeka and Jawa Pos taken by 1-31 January 2014 in reporting DKI Jakarta flooded. Based on the newspapers proportion in reporting DKI Jakarta flooded, I applied purposive sampling in deciding the object of the research. The research use framing analyzes by Robert M. Entman to achieve the goal. The findings of the analysis can be seen as follows: First, Jokowi's failure is not used by Suara Merdeka newspaper as a frame. Yet, Jawa Pos use frame Jokowi's failure in reporting DKI Jakarta flooded. Second, as problem identification, DKI Jakarta flooded is taken as force majeure and has no negative value towards Jokowi by Suara Merdeka. Jawa Pos seen the flood as Jokowi's failure dan has negative value to Jokowi. Third, the weather and tidal flood is used by Suara Merdeka as the most responsible factor for causal interpretation. In Jawa Pos, Jokowi has not been ready, yet. Fourth, Suara Merdeka considered the flooded as natural disaster so that Jokowi has no responsible of it for moral evaluation. Jawa Pos takes DKI Jakarta flooded so seriously and Jokowi has responsible to overcome it. Suara Merdeka offered handling and preventing in treatment recommendation. Jawa Pos asked Jokowi to stay as DKI Jakarta Governor to overcome the flood. Thus, Jokowi is not proper to go on presidential election.